GP227 Clinical spectrum of classical galactosaemia associated with friedreich's ataxia in a paediatric cohort in the republic of ireland – an update. (June 2019) - Boruah, Ritma; Siobhan, Siobhan; Franklin, Orla; Rourke, Declan O'; Lynch, Bryan; Lynch, Sally Ann; Hughes, Joanne; Monavari, Ahmad A; Crushell, Ellen; Knerr, Ina
Abstract : Despite early diagnosis through Newborn Bloodspot Screening and strict dietary treatment, there are long-term complications of Classical Galactosaemia, including female infertility, osteopenia, and, in some cases, learning disabilities or neurological symptoms such as tremor or ataxia. Therefore, neurological symptoms may easily be attributed to an underlying diagnosis of Classical Galactosaemia. However, the coexistence of classical Galactosaemia and Friedreich's Ataxia (FRDA) was previously reported amongst the Irish Traveller population. Classical Galactosaemia and FRDA are both autosomal recessive conditions, the gene loci for which are located on either side of the centromere of chromosome 9. FRDA is one of the most common forms of autosomal-recessive ataxia and slowly progressive; it also commonly involves the heart. We here present the clinical spectrum of 10 Irish patients currently being treated in our Metabolic Centre in whom a diagnosis of Classical Galactosaemia together with FRDA was made. All patients were diagnosed with Classical Galactosaemia through Newborn Screening first. All were diagnosed with the common Classical Galactosaemia GALT mutation Q188R/Q188R. Eight of the ten patients later presented with progressive ataxia, between the ages of 7–14 years. One child presented in cardiac failure secondary to dilated cardiomyopathy at 7 years of age. It was noted that he was not ataxic at presentation of FRDA and that he had normal tendon reflexes. Another patient who was diagnosed at 6 years of age still had an essentially normal neurological exam almost 4 years later. The diagnosis of FRDA was confirmed by detecting the common pathogenic GAA repeat expansion mutations in both alleles of the frataxin gene (FXN) in affected individuals. Taken together, neurological signs may easily be attributed to an established diagnosis of Classical Galactosaemia. However, one should be vigilant for the coexistence of Classical Galactosaemia and FRDA in a high-risk population, particularly when monitoring patients with a complex phenotype, such as a neurological or cardiac presentation.